2014
DOI: 10.1016/j.bbrc.2014.03.071
|View full text |Cite
|
Sign up to set email alerts
|

Digitalis-induced cell signaling by the sodium pump: On the relation of Src to Na+/K+-ATPase

Abstract: In addition to performing its essential transport function, the sodium pump also activates multiple cell signaling pathways in response to digitalis drugs such as ouabain. Based mainly on cell-free studies with mixtures of purified Src kinase and Na(+)/K(+)-ATPase, a well-advocated hypothesis on how ouabain initiates the activation of signaling pathways is that there is a preexisting physiological complex of inactive Src bound to the α-subunit of Na(+)/K(+)-ATPase, and that ouabain binding to this subunit disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 19 publications
2
40
2
Order By: Relevance
“…However, subsequently, it was reported that Src kinase is activated either by ouabain or by vanadate with the conclusion that Src kinase activation is dependent on the energetic state of Na,K-ATPase, in particular the ATP/ADP ratio (18). Similarly, it was reported recently that all three inhibitors (ouabain, vanadate, and oligomycin) activate Src Tyr-418 autophosphorylation, and it was concluded that Src kinase activation is due primarily to the ATP-sparing effects of the ATPase inhibitors (16). Src kinase activation was also reportedly induced by stabilization of purified renal Na,KATPase using either ouabain or BeF and AlF (11).…”
Section: Prior Reports On Src Kinase Binding To Nak-atpasementioning
confidence: 91%
See 1 more Smart Citation
“…However, subsequently, it was reported that Src kinase is activated either by ouabain or by vanadate with the conclusion that Src kinase activation is dependent on the energetic state of Na,K-ATPase, in particular the ATP/ADP ratio (18). Similarly, it was reported recently that all three inhibitors (ouabain, vanadate, and oligomycin) activate Src Tyr-418 autophosphorylation, and it was concluded that Src kinase activation is due primarily to the ATP-sparing effects of the ATPase inhibitors (16). Src kinase activation was also reportedly induced by stabilization of purified renal Na,KATPase using either ouabain or BeF and AlF (11).…”
Section: Prior Reports On Src Kinase Binding To Nak-atpasementioning
confidence: 91%
“…More recently, other studies have challenged the model of direct interaction between Src kinase and Na,K-ATPase (14,16,17,18) (see "Discussion"). Although several observations raise doubts about the direct interaction model, they do not rule out indirect interactions mediated by other proteins that might be involved in the signaling events.…”
mentioning
confidence: 99%
“…In this model, the Na/K‐ATPase α1 subunit provides the ligand binding site and the associated c‐Src functions as the kinase moiety. It has also been proposed that c‐Src activation is primarily due to an ATP‐sparing effect based on a cell‐free system . While the Na/K‐ATPase inhibitors (vanadate and oligomycin) and ATP/ADP ratio regulate c‐Src activation, a possible interaction between the α1 and c‐Src was not addressed …”
Section: Discussionmentioning
confidence: 99%
“…In this model, the Na/K-ATPase α1 subunit provides the ligand binding site, and associated c-Src provides the kinase moiety. A second model is that c-Src activation is primarily a consequence of an ATP-sparing effect (observed in a cell-free system) [45, 46]. A third model proposes that c-Src transiently interacts with a complex formed between the Na/K-ATPase α1 subunit and caveolin-1[47].…”
Section: The Na/k-atpase: Ion Pumping and Signaling Functionmentioning
confidence: 99%